Comparative proteomic analysis of a membrane-enriched fraction from flag leaves reveals responses to chemical hybridization agent SQ-1 in wheat - Song, Qilu; Wang, Shuping; Zhang, Gaisheng; Li, Ying; Li, Zheng; Guo, Jialin; Niu, Na; Wang, Junwei; Ma, Shoucai (Frontiers in Plant Science, 2015)
The induction of wheat male fertile lines by using the chemical hybridizing agent SQ-1 (CHA-SQ-1) is an effective approach in the utilization of heterosis; however, the molecular basis of male fertility remains unknown. Wheat flag leaves are the initial receptors of CHA-SQ-1 and their membrane structure plays a vital role in response to CHA-SQ-1 stress. To investigate the response of wheat flag leaves to CHA-SQ-1 stress, we compared their quantitative proteomic profiles in the absence and presence of CHA-SQ-1. Our results indicated that wheat flag leaves suffered oxidative stress during CHA-SQ-1 treatments. Leaf O2-, H2O2, and malonaldehyde levels were significantly increased within 10 h after CHA-SQ-1 treatment, while the activities of major antioxidant enzymes such as superoxide dismutase, catalase, and guaiacol peroxidase were significantly reduced. Proteome profiles of membrane-enriched fraction showed a change in the abundance of a battery of membrane proteins involved in multiple biological processes. These variable proteins mainly impaired photosynthesis, ATP synthesis protein mechanisms and were involved in the response to stress. These results provide an explanation of the relationships between membrane proteomes and anther abortion and the practical application of CHA for hybrid breeding.